Productivity of Vannamei Shrimp Cultivation (Litopenaeus vannamei) in Intensive Ponds in Tegal City, Central Java Province - Muchtar Muchtar; Mochammad Farkan; Mugi Mulyono (Department of Aquaculture, 2021)
The failure of tiger shrimp (Penaeus monodon) farming could make farmers stop their cultivation activities. As an alternative, vannamei shrimp cultivation gives hope for productive, profitable, and sustainable cultivation. The development of shrimp farming in Tegal City is carried out through simple methods, intensive technology, and the use of Busmetik technology or mini-scale shrimp farming on plastic ponds. The high demand in the shrimp market continues to encourage farmers to increase their productivity by increasing stocking density. The purpose of this study is to determine the performance of vannamei shrimp cultivation which is cultivated intensively including yields, survival rate (SR), feed conversion ratio (FCR), and shrimp growth in Tegal City, Central Java Province. The research was conducted from July to October 2019. The research method used was a case study with 16 plots of ponds, and the average area of the pond was 1000 m². Based on the results of the calculation, it can be seen that the average yield is 1,603 kg per pond with a stocking density of 100 fish/m², a survival rate (SR) is 85.6%, a feed conversion ratio (FCR) is 1.41 and the shrimp growth is 0.16 grams per day. Economically, based on the Benefit-Cost Ratio (B/C ratio) of 1.46, vannamei shrimp cultivation in Tegal City is profitable so that shrimp farming can be carried out sustainably.